Development of a Basic Laws of Chemistry Module Based on TPACK Integrated Guided Discovery Learning for Phase E of Senior High School - Yuda, Sulistiya (Universitas Negeri Padang, 2025)
This study aims to analyze the validity and practicality of the chemistry basic law module based on Guided Discovery Learning integrated with TPACK for high school phase E. The study uses the Research and Development (RD) method with the Four-D (4D) model. The subjects of this study consist of three lecturers, two teachers, and 31 students. The instruments used include observation sheets, interviews, and validity and practicality questionnaires. The data analysis techniques for validity testing were analyzed using the Aiken's V formula, and practicality testing was analyzed using the percentage of practical product achievement scores. The results showed an average Aiken's V value of 0.933, categorized as valid, and the practicality values by teachers and students were 93% and 91%, respectively, categorized as very practical. The research results indicate that the chemistry basic law module integrated with TPACK for high school phase E is valid and practical. To ensure this module can be optimally applied in learning, it is recommended that future researchers continue the study to the effectiveness testing stage.